Using digital platforms to promote a healthcare provider community of practice for abortion care in Uganda - Dan Kabonge Kaye; Simon Peter Kayondo; Stella Lovina Nabatanzi; Susan Nassuuna; Othiniel Musana; Imelda Namagembe; John Paul Nsanja; Othman Kakaire; Peter Ssebadduka; Cissy Ssekimpi (BMC, 2023)
Abstract Background A community of practice (CoP) is defined as a group of people who share a concern, set of problems, or a passion about a topic, and who deepen their knowledge and expertise by interacting on an ongoing basis. The paper presents a case study on the design, implementation and management of a CoP. The objective is to share experiences, opportunities, challenges and lessons learnt in using digital platforms for clinical mentorships to establish a CoP that promotes enhanced service provision of abortion care. Methods We employed competence-based training and ongoing virtual mentorship for abortion care, employing the abortion harm reduction model, and using several digital platforms to create and nurture community of practice for abortion care. Using the Capability-Opportunity-Motivation for Behavior (COM-B) model and textual data analysis, we evaluated the performance of the CoP as a tool to support abortion care, using data from in-depth interviews and information shared on the platforms. The data was analyzed by thematic analysis using text data analytical approach. Results CoPs have much unrealized potential for networking to improve abortion care, as they are more inclusive, interactive and equalizing than typical webinars, yet less expensive and can complement (though not replace) physical mentorships. CoPs' focus on sharing best practices and creating new knowledge to advance professional practice, faces challenges of maintaining regular interaction on an ongoing basis. CoP members need to share a passion for their practice and mutual trust is key to success. Conclusion Though it faced initial challenges of connectivity, and limited interaction, the CoP approach using digital platforms promoted shared experiences, personal connections, communication, collaboration and application of knowledge for improved abortion care.